The influence of service quality on the Aceh government SIGAP website - Irham Maulida; Ulung Pribadi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The Aceh Government's SIGAP website can also be measured by looking at service quality. The influence of service quality on the Aceh Government's SIGAP website as a form of E-Governance application in collecting data and information about Villages. The aim of this research is to analyze the influence of Involvement, Responsiveness, Reliability, and Security on Service Quality of the SIGAP website and to analyze the influence of Service Quality on E-Government. The research method uses probability sampling techniques with stratified random sampling. Research questionnaires were distributed to 6 districts/cities in Aceh Province with a research sample of 128 respondents. Data analysis in this study used Partial Least Squares with the SmartPLS.3.0 application. The research results show that involvement has a positive and significant effect on service quality. The influence of Responsiveness, Reliability, and Security on service quality has a positive but not significant effect. Meanwhile, the influence of service quality on E-Government has a very positive and significant influence.